Миграционные потоки на юге Западно-Сибирской равнины в переходное от бронзы к железу время - Молодин, В.И. (Археологія і давня історія України, 2019)
В статье, посвященной юбилею видного ученого-скифолога С. А . Скорого, рассмотрены миграционные процессы, зафиксированные при помощи
археологических данных на археологических памятниках переходного от бронзы к железу времени
на юге Западно-Сибирской равнины, в лесостепном
Обь-Иртышском междуречье. Определены основные векторы проникновения мигрантов на данную
территорию и их адаптацию в среде аборигенного населения. Главной причиной миграций является географический фактор. The article is dedicated to anniversary of a brilliant scientist, an outstanding scythologist S. A. Skoryy. I suppose
this essay, devoted to the Early Scythian period in the south of West Siberian Plain, will be interesting for
our hero of the day. The atricle present the reconstruction of migration flows during the Late Bronze to Iron Age
transition in the south of West Siberian plane based on archaeological data from Chicha 1 and Bolshoy Log settlements.
The main vectors of migration flows, revealed and described in this article, indicate a strong penetration
of different archaeological cultures to the Ob-Irtysh forest steppe. The bearers of Suzgun, Atlym, Berlik and
other cultures that occupied nearby territories for more than two centuries have adapted to aboriginal late Irmen
population. The Ob-Irtysh area was an attractive place for living. The abundant pastures with a stable herbage
yields and the wealth of fish and game equally attracted both herdsmen and fishermen-hunters. Apparently, during
this time the migration flows changed their directions and didn’t get in each other’s way. The mosaic of cultural
formations peacefully shared Ob-Irtysh area was developed in the south of West Siberian plane during Bronze
to Iron Age transition. This has been possible because of the different orientation of paleoeconomy of these societies.
Besides, it must be noted that the bearers of aboriginal late Irmen culture were quite tolerant. They involved
newcomers in their influence arena and even lived with them on the one living space area, e. g. on settlements.
This evidence of this behavior was discovered on Chicha 1 and Bolshoy Log sites for instance.